2020
DOI: 10.18203/2394-6040.ijcmph20203941
|View full text |Cite
|
Sign up to set email alerts
|

Health seeking behaviour of geriatric population in rural area of Puducherry: a community based cross sectional study

Abstract: Background: Population ageing is a great concern for the health sector. The health-seeking behaviour of elderly individuals can help in ascertaining their needs and priorities to develop appropriate policies for their care and avert disease progression. Objective was to assess health seeking behaviour of the elderly residing in rural Puducherry.Methods: A community based cross-sectional descriptive study was conducted among the geriatric population residing in selected areas of rural Puducherry. Interviews usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Health-seeking behavior (HSB) is an important concept associated with a country's health status and economic development [1]. It also helps uncover the health needs and priorities of a population and informs the development of appropriate policies to address their needs and avert their disease progress [2]. In the literature, HSB has been studied with different scopes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health-seeking behavior (HSB) is an important concept associated with a country's health status and economic development [1]. It also helps uncover the health needs and priorities of a population and informs the development of appropriate policies to address their needs and avert their disease progress [2]. In the literature, HSB has been studied with different scopes.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, HSB has been studied with different scopes. The most commonly used definition is "any action or inaction undertaken by individuals who perceive themselves to have a health problem or to be ill for the purpose of finding an appropriate remedy" [3], and studies adopting this definition always examined the formal health system use or the process of illness responses [2,[4][5][6]. However, one could argue that this definition focuses mainly on illness behaviors [7] and ignores the importance of promoting overall health and well-being, as health is not merely the absence of disease or infirmity but rather a state of complete physical, mental, and social well-being [8].…”
Section: Introductionmentioning
confidence: 99%
“…51.7% of them were utilizing Government health care facilities which include Government hospital, PHC and sub-centers. 29 Maroof et al in their study in Aligarh also found 73.1% (285/390) elderly using allopathic system of medicine for illness. 30 Another important factor regarding health seeking behaviour of rural elderly is using over the counter medication from medical stores & quacks.…”
Section: Discussionmentioning
confidence: 92%
“…The Present study showed that 59.8% study subjects in rural and 77.6% in urban areas availed treatment, and overall, 72.7% study subjects availing treatment. A study by Gnanasabai G et al (9) showed that 81.1 % study subjects were taking treatment. In Our study 27.8% females in rural areas and 53.0% females in urban areas availed treatment.…”
Section: Discussionmentioning
confidence: 98%